Efficacy of external warming in attenuation of hypothermia in surgical patients - Zeba, Snježana; Šurbatović, Maja; Marjanović, Milan; Jevdjić, Jasna; Hajduković, Zoran; Karkalić, Radovan; Jovanović, Dalibor; Radaković, Sonja (Vojnosanitetski pregled, 2017)
Background/Aim. Hypothermia in surgical patients can be the consequence of long duration of surgical intervention, general anaesthesia and low temperature in operating room. Postoperative hypothermia contributes to a number of postoperative complications such as arrhythmia, myocardial ischemia, hypertension, bleeding, wound infection, coagulopathy, and prolonged effect of muscle relaxants. External heating procedures are used to prevent this condition. The aim of this study was to evaluate the efficiency of external warming system in alleviation of cold stress and hypothermia in patients who underwent major surgical procedures. Methods. The study was conducted in the Military Medical Academy in Belgrade. A total of 30 patients of both genders underwent abdominal surgical procedures, randomly divided into two equal groups: the one was externally warmed using warm air mattress (W), while in the control group (C) surgical procedure was performed in regular conditions, without additional warming. Oesophageal temperature (Te) was used as indicator of changes in core temperature, during surgery and awakening postoperative period, and temperature of control sites on the right hand (Th) and the right foot (Tf) reflected the changes in skin temperatures during surgery. Te and skin temperatures were monitored during the intraoperative period, with continuous measurement of Te during the following 90 minutes of the postoperative period. Heart rates and blood pressures were monitored continuously during the intraoperative and awakening period. Results. In the W group, the average Te, Tf and Th did not change significantly during the intraoperative as well as the postoperative period. In the controls, the average Te significantly decreased during the intraoperative period (from 35.61 ± 0.35ºC at 0 minute to 33.86 ± 0.51ºC at 120th minute). Compared to the W group, Te in the C group was significantly lower in all the observed periods. Average values of Tf and Th significantly decreased in the C group (from 30.83 ± 1.85 at 20th minute to 29.0 ± 1.39ºC at 120th minute, and from 32.75 ± 0.96 to 31.05 ± 1.09ºC, respectively). Conclusion. The obtained results confirm that the external warming using warm air mattress was able to attenuate hypothermia, i.e. substantial decrease in core temperature, compared with the similar exposure to cold stress in the control group.
Keywords: anesthesia; general; digestive system surgical procedures; hypothermia; intraoperative period; postoperative complications; monitoring; physiologic; heating